Sustainability assessment of different pipeline materials in freshwater supply systems - Chohan, Imran Mir; Ahmad, Azlan; Bheel, Naraindas; Najeh, Taoufik; Almaliki, Abdulrazak H. (Frontiers in Materials, 2025)
Freshwater supply systems are considered as an important component within urban water systems. Although the development of freshwater supply systems may have significant impact on the environment, there have been only a few studies examining its environmental effects. This paper assesses the environmental impact of four pipeline materials in freshwater supply system using life cycle assessment following ISO 14040–14044 standards. The SimaPro 9.6.0.1 software was used for life cycle analysis. The results indicated that steel has a greater environmental impact in most impact categories during the pipe manufacturing phase than other pipeline materials. During the installation phase, two types of trenches were considered for plastic pipelines and steel pipelines installation and found that the plastic pipe trench experiences its greatest impact during installation phase. To showcase the practicality of the suggested approach, a segment of the Seri Iskandar freshwater supply system was chosen as a case study. The findings revealed that by substituting a portion of the pipes with environmentally sustainable materials, the environmental impact during manufacturing and materials phase of pipelines used for construction of FWSS can be reduced by 14% in fossil resource scarcity, 19% in ozone layer depletion, 20% in ionization radiation, 22% in climate change, and 25% in marine ecotoxicity potential.